x^2-y^2-z^2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^2\left(y^2+z^2-x^2\right)+y^2\left(z^2+x^2-y^2\right)+z^2\left(x^2+y^{ 2}-z^2\right)\)
\(=x^2\left[\left(y+z\right)^2-x^2-2yz\right]+y^2\left[\left(z+x\right)^2-y^2-2zx\right]+z^2\left[\left(x+y\right)^2-z^2-2xy\right]\)
\(=x^2\left[\left(y+z-x\right)\left(y+z+x\right)-2xy\right]+y^2\left[\left(z+x-y\right)\left(z+x+y\right)-2zx\right]\)
\(+z^2\left[\left(x+y-z\right)\left(x+y+z\right)-2xy\right]\)
\(=x^2\left[\left(y+z-x\right).0-2yz\right]+y^2\left[\left(z+x-y\right).0-2zx\right]+z^2\left[\left(x+y-z\right).0-2xy\right]\)
\(=x^2\left(-2yz\right)+y^2\left(-2zx\right)+z^2\left(-2xy\right)\)\(=-2x^2yz-2xy^2z-2xyz^2\)
\(=-2xyz\left(x+y+z\right)=-2xyz.0=0\)
bạm oi đay đau phải câu hỏi